Analisis Faktor-Faktor yang mempengaruhi hasil Produksi Padi di Desa Jangan- Jangan Kecamatan Pujananting Kabupaten Barru - Lisa, Lisa; Akhmad, Akhmad; Asriati, Asriati (Universitas Teuku Umar, 2025)
This study aims to analyze the factors affecting rice production in Jangan-Jangan Village, Pujananting District, Barru Regency. The factors examined include land area, labor usage, and pesticide application. Data were collected from 20 farmer respondents through surveys and analyzed using multiple linear regression. The results show that land area and pesticide use have a positive and significant effect on rice production, while labor does not have a significant effect. The coefficient of determination (Adjusted R Square) of 0.679 indicates that 67.9% of the variation in rice production can be explained by the three variables, while the remaining 32.1% is influenced by other factors outside the model. Keywords: rice production, land area, labor, pesticides